Science World [motion pictures] Space science : planets; - comets, meteors and asteroids; - galaxies and the universe. - Coronet (Northbrook, IL Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.
Vol. 17: Planets; - Comets, meteors and asteroids; - Galaxies and the universe
Original copy in VHS format (VHS 17)
[Distributed by] International Book Center, Philippines
Keywords: Galaxies; Cosmology; Planets